Perioperative use of high flow nasal cannula: High flow nasal cannula during perioperative care - Visuthisakchai, Suharit; Kongsayreepong, Suneerat (Clinical Critical Care, 2024)
High flow nasal cannula (HFNC) is an innovative oxygen therapy system that has gained increasing popularity in recent decades, particularly in the field of critical care medicine. The device provides a more constant and higher FiO2, generates low levels of PEEP, reduces dead space ventilation, and conditions the inspired gas, which collectively results in a reduction in work of breathing (WOB) and improved patient comfort. While the application of HFNC in critically ill patients is well-established and supported by a large body of evidence, studies of HFNC during the perioperative period are limited. However, the working mechanisms of HFNC align with physiological demands across various anesthetic processes. Consequently, this system could potentially serve as an alternative oxygen delivery system for surgical patients during perioperative care. In this article, we summarize the working principles and the effects provided by HFNC, review its implementation during the perioperative period, and discuss the current evidence regarding its use.